(untitled) (World Economics and Finance Bulletin, 2024)
Industrial expansion has led to an increase in the volume and quality of industrial pollutants resulting from the industrial sector. These pollutants are necessarily reflected in the destruction of the natural environment, and this has helped the emergence of the modern concept of sustainable development, which means the pattern of development that seeks to achieve the welfare of society without harming the environment and its resources, This modern concept of development has been reflected on many sciences, including accounting sciences, and this resulted in addressing the financial and accounting implications of the issue of environmental pollution by the branches of accounting and among these branches comes tax accounting. Therefore, specialized scientific studies have highlighted since the sixties of the twentieth century the seriousness of environmental pollution and the search for ways to address and protect the environment by adopting the environmental tax system as a means of confronting environmental pollution and reducing it economically, as environmental taxes are mandatory uncompensated payments, the proceeds of which are due to the general budget of the state. The imposition of environmental taxes contributes to tax reform processes. Therefore, they affect the tax structures resulting from their imposition, and they also contribute to the process of improving and protecting the environment. Therefore, the question arises regarding the role that the tax system, with its various tools, can play in terms of positively influencing the decisions of economic units from controlling pollution levels associated with productive activities in order to reduce pollution levels to acceptable limits. Therefore, this study revolves around four axes, namely, the first axis reviews the costs of environmental pollution and the problems of measuring it, the second axis is devoted to the tools of the tax system, the third axis deals with environmental pollution taxes and global experiences, and the fourth axis is devoted to application in Iraq. This study found the need to amend the existing tax system in Iraq after the introduction of environmental taxes within the tax structure to achieve tax balance by reducing some of the usual taxes, such as income tax on workers